A Racialized Researcher Facing a Differentiated Racial Subjectivity: Clinical and Reflexive Approach to Racism (Clinical Sociology Review, 2025)
For a racialized researcher, investigating racism can seem perilous from the perspective of the relationship to the object required by a scientific objectification approach. This reflexive article is based on an ethnography that links my biography to a clinical approach in order to access the racist experience of different racialized groups in France (social work students and residents of working-class neighborhoods). This approach, both reflexive and clinical, requires a patient and attentive construction of the conditions of enunciation of the experience in order to identify the tensions between identity for oneself and identity for others. It allows for the comparison of similar experiences, sometimes lived differently depending on life history and the frequency of racist offenses and attacks. The article's theme questions the ambivalence of my ethnoracial identification with minority groups, a relationship that takes the form of a play of similar or discordant perceptions. Identity misalignments in the field are a particular source of reflexivity, especially since being racialized does not necessarily offer an epistemic advantage in accessing minority experiences. In a context of denial of systemic racism, transference and countertransference (Devereux, 1967) reflect the sharing of a stigmatized identity—a racialized self—with subjects who do not initially consider themselves racialized. These contrasting ways of recognizing oneself in the experience of racialization are the result of a differentiated learning of a racialized self, which is revealed or reinforced in the research interaction. Countertransference, in particular, made it possible to make a differentiated racial subjectivity visible.
Keywords: Clinical sociology; social identity; reflexivity; racial subjectivity; transference; countertransference